Adapting the Serbian economy to regional and European integration - Vesić Dobrica (Međunarodni Problemi)
In contemporary international relations, economic activities are becoming increasingly prioritized in relation to political ones. For Serbia, it is important to have a clear strategy of development that will have significant implications for all economic activities and international economic cooperation, i.e. the process of European integration. In creating the development strategy it is necessary to choose the sectors of the economy on which the future development of the Serbian economy will be based. On the other hand, instead of maximizing profits and due to the creation and strengthening of several relevant groups of stakeholders (managers, employees, customers, the state, etc.) whose long-term interests must be taken into consideration by a company, it is primarily through harmonization of their interests that pluralism and complexity of goals of a contemporary corporate company is achieved. Attaining of the set goals in the radically changed and highly competitive market environment demands to formulate strategies based on a detailed analysis of the macroeconomic and microeconomic environment, resources and other business potentials. It should be noted that there have been identified three phases of competitiveness of a country and these are as follows: factor-driven, efficiency-driven and innovative-driven competitiveness. In its development every country should go through competitiveness based on the supply of factors of production through investment driven competitiveness based on the efficiency of use of available factors of production to innovation driven competitiveness. [Projekat Ministarstva nauke Republike Srbije, br. 179029: Srbija u savremenim međunarodnim odnosima: Strateški pravci razvoja i učvršćivanja položaja Srbije u međunarodnim integrativnim procesima -spoljnopolitički, međunarodno ekonomski, pravni i bezbednosni aspekti]